2016
DOI: 10.1002/cben.201600004
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich Packings: State of the Art

Abstract: Capacity and efficiency of packed columns can be significantly improved by the application of sandwich packings. An element of such packings consists of two alternating layers of industrially available standard packings with different specific surface areas. Sandwich packings are commonly used for operating conditions between the flooding points of both layers, with a heterogeneous flow pattern established along a sandwich packing element. There are some similarities between this flow pattern and those in conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…Assuming a comparable froth height in each de‐entrainment layer (except the lowest one in which no froth regime evolves), the height of the froth regime H Fr in each sandwich stack is determined to be only 8 mm according to Flechsig et al . Whereas the experimentally obtained heights agree very well (60 mm and 61 mm), the correlation (8 mm) clearly underpredicts the experiments for the selected loads.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Assuming a comparable froth height in each de‐entrainment layer (except the lowest one in which no froth regime evolves), the height of the froth regime H Fr in each sandwich stack is determined to be only 8 mm according to Flechsig et al . Whereas the experimentally obtained heights agree very well (60 mm and 61 mm), the correlation (8 mm) clearly underpredicts the experiments for the selected loads.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison with an existing empirical correlation by Flechsig at al. revealed that the correlation clearly underpredicts the experimental data if column and packing dimensions, loading limits, and pressure drop level are different. However, the froth height meets the experimental results when the same pressure drop at an appropriate higher gas load is applied or the characteristics of the small‐scale column are properly considered in the correlation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Höhe des Sprudelsegments in der AN ist gleich der gesamten Höhe der AN. Die Höhe der Sprudelschicht in der AB wird durch eine empirische Korrelation berechnet, in der die Geschwindigkeiten beider Phasen, geometrische Parameter der AP und Stoffeigenschaften berücksichtigt werden : true right1 HnormalSPRnormal,normalAB left = HnormalAB ( FG - FG,FP AN FG,FP AP - FG,FP AN )[ln( unormalL ρnormalL dnormalh normalAB ηnormalL ) K1 + K2 ] right1 left × ( dnormalh normalAN dnormalh normalAB ) normalK3 …”
Section: Rate‐based Konzept Für Anstaupackungenunclassified